Murder in the garment district : the grip of organized crime and the decline of labor in the United States - Witwer, David Scott; Rios, Catherine (The New Press, 2020)
"The thrilling and true account of racketeering and union corruption in mid-century New York, when unions and the mob were locked in a power struggle that reverberates to this day"--